Technological Innovation In Insulin Delivery: A comprehensive Review of Emerging solutions for Diabetes Management - Ibrahim, O.M et al. (International Journal of Scientific Research and Innovative Studies, 2024)
The bad and ugly part of metabolic fuel in human body is the health impairment termed Diabetes which is non-infectious silent killer that has subjected human galaxy to high morbidity and mortality. Synthetic insulin delivery methods for ameliorating the effect caused by diabetes remains in the fore-front of development geared towards miniaturizing and getting user-friendly approach in curbing the pain and penury associated with Diabetes. There is evolution over the years from the crude insulin delivery tools to present day technological advancement of delivery system that dispense insulin to the systemic circulation which mimic the natural and physiological potency in management of the glycemic level in real time. The future landscape is aimed towards providing an automated technological panacea that is cost effective, efficient in monitoring and maintenance of the physiological level of glucose in real time scenario. Key words: Glucose metabolism, Insulin therapy, New Technology, Type 1 and Type 2 Diabetes. Received Date: November 05, 2024 Accepted Date: November 26, 2024 Published Date: December 01, 2024 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/262 https://doi.org/10.5281/zenodo.14261032